Estudo comparativo da genotoxicidade do antirretroviral abacavir isolado e em combinação com zidovudina e lamivudina in vivo - Carvalho, Cláudia de Jesus Silva (2015)
Abacavir (ABC), zidovudine (AZT) and lamivudine (3TC) are nucleoside reversetranscriptase inhibitors (NRTIs) widely used as the main axis of highly active antiretroviral therapy (HAART). Despite the effectiveness of combinations of NRTI in viral suppression, there is evidence to show that the genotoxic potential of NRTIs can be increased when administered in combination. In this context, this study proposed to investigate the toxic and genotoxic potential ABC induced when administered isolated and in combination with AZT and/or 3TC, using the wing SMART in Drosophila melanogaster. This test simultaneously evaluates two events related to carcinogenesis, mutation and somatic recombination, and is based on the identification of the mutants hairs resulting from lesions that lead to loss of heterozygosity in two marker genes involved in the formation of the wings of hair: mwh and flr3. In toxicity tests, groups of 100 larvae of third instar from the standard cross were treated for 48 hours with different concentrations of drugs. From the results obtained,was established a range of concentrations presenting more than 70% of survivors flies to proceed the analysis of genotoxicity. Employing the conditional binomial test, were compared the spots of mutants hair frequencies present in trans-heterozygotes and heterozygous flies for chromosome TM3 of each treated group with the respective controls. The results of investigations indicated that ABC was toxic to larvae in concentrations greater than 2 mg/ml. The combinations which contained ABC showed toxic effects similar to isolated ABC. All treatments were able to induce genetic alterations related to mutation and somatic recombination. Among all combinations, AZT/3TC was the one that showed less toxic and genotoxic potential at the concentrations tested. The potential recombinogenic both ABC isolated or in combination was relatively high, with indices of over 83.7%.